INFLUENCE OF THE INTERNAL STRUCTURE OF THE BUILDING MATERIAL ON THE DRYING PROCESS (American Journal of Technology and Applied Sciences, 2023)
In the article, molecular physics related to the significant progress achieved at the atomic-molecular level, as well as the wide use of new physics, a deeper penetration into the essence of microprocesses in the construction processes and the consideration of corpuscular models depending on the atomic-molecular structure, molecules, atoms, ions that form wet materials, it is recommended to take into account the interaction forces between bodies.